Differential potentiation of odor aversion and yawning by melanocortin 4 receptor signaling in distinct regions of the ventral striatum - Alam, Md Tasnim; Ahasan, Md Monjurul; Shimizu, Shogo; Murata, Yoshihiro; Taniguchi, Mutsuo; Yamaguchi, Masahiro (Frontiers in Neuroscience, 2025)
Although animal behavior is influenced by neuromodulatory signals, the underlying mechanism remains elusive. The ventral striatum, which consists of the olfactory tubercle (OT) and nucleus accumbens (NAc), promotes motivated behaviors and receives substantial neuromodulatory signals. We previously showed that the OT has anteromedial (am) and lateral domains regulating odor-guided attractive and aversive behaviors, respectively, in which the amOT highly expresses various receptors for feeding-regulated neuromodulators. Here, we investigated the functions of appetite-suppressing melanocortin 4 receptor (MC4R) signaling in the OT as well as in the NAc. When mice conditioned with an odor-food reward association underwent MC4R agonist injection in the amOT, their odor-attractive behavior was suppressed and odor-aversive behavior was induced. Conversely, injection of MC4R antagonist in the amOT induced attractive behavior to a neutral odor that was not associated with food reward. While MC4R agonist injection in the NAc shell did not influence odor-attractive behavior, it induced yawning and stretching behaviors. Consistent with a proposed role of these behaviors in the thermoregulation of the brain, recordings of brain temperature showed its occasional elevation after agonist injection, followed by the occurrence of yawning and stretching. These observations demonstrate the differential roles of MC4R signaling in the ventral striatum, the promotion of odor-aversive behavior in the amOT, and yawning/stretching behavior in the NAc, which are considered to collectively contribute to behavioral control under feeding.